NEW HOPE IN A NEW LAND - Suprihandari, Miya Dewi; Setyawan, Mochamad Ardi; Purnomo, Teguh; Abdillah, Hasan (Transpublika Publisher, 2023)
Home is an essential sanctuary for all living beings, holding profound significance regardless of time or place. Ensuring the well-being of our habitation sites is imperative, necessitating vigilant protection and prudent care. Both local and central governments have embarked on diverse avenues to secure improved living conditions in novel environments. This paper endeavors to illuminate the landscape of capacity building initiatives and improved environmental conditions, encompassing not only the current inhabitants but also extending to the broader community. These endeavors harbor long-term implications, benefiting society and governance structures, and casting a positive influence on forthcoming generations. The responsibility of the succeeding generation lies in the preservation, cultivation, and effective management of newfound environmental potential, offering benefits to all stakeholders. Equipping communities and future generations with the requisite training to harness and nurture environmental resources emerges as a pivotal strategy in realizing this potential.